The Process and Meaning of the Manusa Yadnya Ceremony for the Hindu Bali Community - I Nengah Suastika (International Journal of Social Science and Business, 2021)
The Balinese Hindu community interpret life as a process of transformation that must always be interpreted and treated. According to the beliefs of the Balinese Hindu community, the process of the life cycle to achieve the perfection of life must go through various stages of the procession of the ceremony (the ceremony of manusa yadnya). Life cycle ceremony processions carried out since the fetus is still in the womb, born, large, adult, old, even to death. It is believed that it is not only the body that needs nutritionally complete and balanced food in its growth and development. Spiritual must also be given spiritual food to build spiritual growth itself toward a healthy, strong and steady spirit. The life cycle ceremony process is a process of spiritual self-cleansing to lead to physical and spiritual purity. In the Book of Manawa Dharmasastra the life cycle ceremony process is stated as samskara sarira. Sarira samkara means a ceremony to increase the sanctity of one's body through the process of yadnya (holy sacrifice) ceremony. To achieve this increase should be balanced growth between the body (sarira) physical and spiritual. Corresponding to that, then studying the ceremonial procession and the meaning of the ceremony procession of the Hindu Balinese human life cycle is something very urgent.